Optional law : the structure of legal entitlements - Ayres, Ian, 1959- (University of Chicago Press, 2005)
Spurred by the advances in option theory that have been remaking financial and economic scholarship over the past thirty years, a revolution is taking shape in the way legal scholars conceptualize property and the way it is protected by the law. Ian Ayres's Optional Law explores how option theory is overthrowing many accepted wisdoms and producing tangible new tools for courts in deciding cases. Ayres identifies flaws in the current system and shows how option theory can radically expand and improve the ways that lawmakers structure legal entitlements.